Organization of the Human Trichromatic Cone Mosaic - Hofer, Heidi; Carroll, Joseph; Neitz, Jay; Neitz, Maureen; Williams, David R (The Journal of neuroscience, 2005)
Using high-resolution adaptive-optics imaging combined with retinal densitometry, we characterized the arrangement of short- (S), middle- (M), and long- (L) wavelength-sensitive cones in eight human foveal mosaics. As suggested by previous studies, we found males with normal color vision that varied in the ratio of L to M cones (from 1.1:1 to 16.5:1). We also found a protan carrier with an even more extreme L:M ratio (0.37:1). All subjects had nearly identical S-cone densities, indicating independence of the developmental mechanism that governs the relative numerosity of L/M and S cones. L:M cone ratio estimates were correlated highly with those obtained in the same eyes using the flicker photometric electroretinogram (ERG), although the comparison indicates that the signal from each M cone makes a larger contribution to the ERG than each L cone. Although all subjects had highly disordered arrangements of L and M cones, three subjects showed evidence for departures from a strictly random rule for assigning the L and M cone photopigments. In two retinas, these departures corresponded to local clumping of cones of like type. In a third retina, the L:M cone ratio differed significantly at two retinal locations on opposite sides of the fovea. These results suggest that the assignment of L and M pigment, although highly irregular, is not a completely random process. Surprisingly, in the protan carrier, in which X-chromosome inactivation would favor L- or M-cone clumping, there was no evidence of clumping, perhaps as a result of cone migration during foveal development.